Diabetes Melitus Tipe 2 - Dei Anjelia Nisa Br Ginting (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
According to the American Diabetes Association (ADA), diabetes mellitus is a chronic and complex disease that requires ongoing management and various strategies to control blood sugar levels and reduce associated risks. Patient Mrs. J, a 52-year-old woman and farmer, presented with complaints of numbness and tingling in both legs that began approximately 2 months prior to her current visit and had worsened over the past week. The symptoms felt like being pricked and sometimes felt hot, especially at night, thereby interfering with daily activities. The symptoms were accompanied by frequent urination, especially at night, frequent thirst, frequent hunger, a feeling of weakness, and intermittent blurred vision. The patient had been diagnosed with diabetes mellitus approximately 5 years ago but did not consistently take medication (glimepiride). The patient still frequently consumes sweet, coconut-based, and fried foods. Physical examination revealed reduced sensation in the lower extremities. Laboratory tests showed elevated blood sugar levels. Based on the medical history, physical examination, and supporting tests, the patient was diagnosed with Type 2 Diabetes Mellitus. The patient was advised to record test results and changes in his health status in a health record book, and to involve family members in supporting treatment adherence and a healthy lifestyle. The patient works as a farmer with an irregular income, depending on the harvest. Daily expenses are shared with his son, so his economic condition